Study of Halal Tourism Village Based on Creative Economy in Canting Village, Landungsari, Pekalongan City - Adinugraha, Hendri Hermawan; Ma’ruf, Hasan (MUAMALATUNA, 2023)
The objectives of this study are to describe how big the potential of the Kampung Canting Landungsari in Pekalongan City is as a representation of a creative economy-based halal tourism village, to explain economic activities in empowering the Kampung Canting Landungsari community as a village that has the potential to become a halal tourism village based on a creative economy, analyzed the concept of a creative economy- based hala tourism village in Kampung Canting Landungsari, Pekalongan City. This research is a type of qualitative research. The data collection method in this study used interviews and observation with a total of 6 informants. The sampling technique was purposive sampling. This research uses a data reduction analysis method. The results showed that the Kampung Canting Landungsari, Pekalongan City has great potential for representing a halal tourism village based on a creative economy. Apart from operating as a tourism center, Kampung Canting Landungsari is an area that is thick with religious culture. Then several main elements must be met to analyze the concept of a Halal Tourism Village based on a creative economy. Several criteria have been met by Kampung Canting Landungsari, but there are still criteria that need to be improved again to become a Halal Tourism Village.